Investigation of P and PD Controllers’ Performance in Control Systems with Steady-State Error Compensation - Levišauskas, Donatas; Tekorius, Tomas (Elektronika ir Elektrotechnika, 2012)
In the paper, performance of P and PD controllers in control systems with steady-state error compensation is investigated and compared with a performance of ordinary PI and PID control systems. The investigation is carried out by computer simulation of the control systems in controlling the processes with various dynamic parameters. Performance of P controller is also investigated by operating in the control system with steady-state error compensation and the control system adaptation to time-varying operating conditions. The investigation results show that that the P and PD controllers in the systems with steady-state error compensation outperform the ordinary PI and PID control systems, respectively. DOI: http://dx.doi.org/10.5755/j01.eee.121.5.1297